Vladimir Lovec v vlogi glasbenega kritika - Ribizel Popič, Tjaša (Muzikološki zbornik, 2024)
Vladimir Lovec was exceptionally versatile. In addition to his creative, pedagogical, artistic, and choir-conducting activities, Lovec’s output also included music criticism, with 88 published music reviews (the extant reviews are kept in the NUK Music Collection) in the newspapers Ljudska pravica, Tedenska tribuna, Slovenski Jadran and Primorske novice. The reviews vary in terms of different factors. Therefore, the aim of the first part of the paper is to analyze the patterns of Lovec’s music criticism in terms of their creation, place of performance, performers, publication and sentiment (i.e. the “tone” of his reviews or his critical reception as such). In the second part, the paper aims to outline Lovec’s style of music criticism.
Keywords: glasbena kritika; glasbena publicistika; music criticism; music journalism; musicology; muzikologija